Serum Triglycerides and Total Cholesterol levels and its Relation with type 2 148 Diabetes mellitus (Journal of Dhaka Medical College, 2020)
Diabetes mellitus is one of the most widespread endocrine disorder in female and its complications are increasing all over the world, leading to life threatening medical problems like cardiovascular diseases, stroke and end stage renal diseases. A relation between hyperlipidemia and diabetes mellitus has been identified. The study was carried out to observe the serum triglycerides and total cholesterol levels its relation with type 2 diabetes mellitus in adult female subjects. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2011 to December 2011. A total number of sixty female subjects were selected with age ranging from30 to50 years. Among them 30 female subjects with diabetes were included from out-patient department of Endocrinology, Dhaka Medical College Hospital, Dhaka as study group(B) and 30 apparently healthy female were taken as control group(A) for comparison. Estimation of fasting serum triglycerides (TG) and total cholesterol (TC) levels were done by enzymatic method in the Department of Physiology, Dhaka Medical College Dhaka in both groups. Fasting serum insulin level was measured by ELISA method in the Department of Laboratory of National Institute of ENT, Dhaka and fasting blood glucose was estimated by glucose oxidase method in Department of Dhaka Medical College in both groups. Data were analyzed by Unpaired Student’s- test and Pearson’s correlation co-efficient (r) test as applicable. The value of fasting serum TG and TC level were significantly higher in study subjects than those of control. In study subjects fasting serum TG and fasting serum TC levels showed positive correlation with fasting blood glucose and serum insulin level.Conclusion: Present study revealed that fasting serum triglyceride (TG) and fasting serum cholesterol (TC) levels have positive relationship with fasting serum insulin and fasting blood glucose levels.J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 148-154